A Case Study Application of Active and Passive Warming to the Patient with Tongue Reconstruction and Frenuloplasty in PACU at the Central Operation Theatre in Hasanuddin University Hospital - Imelda Olviana Lande'eo; Takdir Tahir; Abdul Majid; Syahrul Ningrat (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Introduction: Postoperative hypothermia that occurs in infants may cause several complications. The aspect of thermoregulation management, such as the active and passive warming in patients during the perioperative period, is essential to prevent postoperative complications. Therefore, this study aims to know the application of active and passive warming to patients with tongue reconstruction and frenuloplasty in the Post Anaesthesia Care Unit at the Central Operation Theatre in Hasanuddin University Hospital. Method: A descriptive case study using a single case design method to determine the effectiveness of hypothermia risk management using active and passive warming methods on a patient undergoing tongue reconstruction and frenuloplasty. Data was collected by conducting observations, implementation, and documentation on patients. Results: An active warming method using air-forced equipment with a temperature setting of 38°C was given, and a passive warming method was provided by giving cotton clothes and blankets to the patient. The initial body temperature measurement was 35.5°C. During the evaluation, 30 minutes after the intervention, there was an increase in body temperature to 36°C. During the review, 60 minutes after the intervention, the body temperature rose to 36.6°C; in the last evaluation, 90 minutes after the intervention, the body temperature was increased to 37°C. The patient left the PACU with a body temperature of 37°C. Conclusion: Prevention of hypothermia in postoperative patients is essential, and methods of preventing hypothermia can be used as active warming and passive warming methods.